The Impact of COVID-19 on the Electronic Commerce Users Behavior - Al-maaitah, Tamara Adel; Majali, Tha’er; Alsoud, Malek; Al- maaitah, Dirar AbdelAziz (The journal of contemporary issues in business and government, 2021)
The global coronavirus (COVID-19) pandemic has created an incredibly difficult business climate. Businesses are presented with many new challenges as international borders close, brick-and-mortar businesses shut their doors, and people are told to isolate at home. Many companies face temporary or even permanent closure, with staff facing months of financial uncertainty and concerns. Consumer behavior has been forced to immediately change on a massive scale. People in isolation or under lockdown cannot perform their usual routines, because local shops have been forced to close their doors for safety reasons. Concerns about the availability of goods have encouraged panic buying of items in bulk. Financial uncertainty and the prospect of a severe and long-term recession make for a stark backdrop, which has led to an impact on consumer outlook, perceptions, and behaviors. Around the world, businesses that continue to operate seek the best ways to cope with the prevailing trading conditions and the best ways to adapt their strategies. However, no definite recommendation can be given, because the COVID-19 pandemic is unprecedented. Hence, circumstances are changing fluidly on a daily basis. Defining a strategy now is difficult due to limited evidence or precedent to base assumptions on. Possible business and economic outcomes could be gauged by looking at data from countries that first suffered from the effects of COVID-19. Despite no guarantee that other countries will follow the same trajectory, an analysis of these countries can reveal useful patterns and insights. This research attempts to explore the impacts of the extent of COVID-19 on the e- commerce firms in Saudi Arabia, where the five largest e-commerce firms in the Saudi Arabia were chosen in terms of incomes and market value, This research tests that e- commerce raised due to coronavirus.